One new species and a new record of saprobic fungi from Ananas comosus in northern Thailand - Shah, Sujit; Farias, Antonio Roberto Gomes De (Phytotaxa, 2024)
Pineapple is one of the major crops in northern Thailand. Like all the other plants, it has associated with it, a wide range of fungi, which may be saprobic, pathogenic, or endophytic. This study investigated fungi associated with pineapple in Chiang Rai Province, northern Thailand. Based on morphology and multilocus phylogeny of the ITS and LSU sequence data, Anthracocystis ananatum is described as a new species with its detailed asexual morph. Compared to other Anthracocystis species, A. ananatum has a distinctive morphotype that includes septate hyphae, conidigenous cells, and conidiophores. In addition, Spegazzinia tessarthra is reported for the first time as a new host and geographic record. The complete descriptions, photo-micrographs, and phylogenies of the new species Anthracocystis ananatum and a new host and geographic record S. tessarthra are provided and discussed.